Psychological Attributes of Truants and Non-Truants High School Students of Jammu Region - Kalhotra, Satish Kumar (2013)
The present study is an attempt to find out the relationship of certain socio-psychological variables with the truant behaviour. The sample for conducting the present study included 100 students in class 9th, which include 50 truants and 50 non-truants. Two tools were selected by the researcher namely Dr. S. Jalota and Sharma for general mental ability( 1972) and school satisfaction by Dr. Meenakshi Sharma (1991). T- Test was used to find out relationship. The results reveals that habitual truants and regulars do not differ significantly on the variable of school satisfaction possess lower non-verbal intelligence. The higher level of processors towards truancy among boys may be explained considering the fact that boys have lesser social inhibitions, more parental freedom and less home responsibilities. Key words : Truancy, school phobia, delinquency school satisfaction, intelligences.School Satisfaction